Distribution and abundance of ticks infesting livestock population along Karakorum highway from Mansehra to Gilgit, Pakistan - SAJID, MUHAMMAD SOHAIL; IQBAL, ZAFAR; SHAMIM, ASIM; SIDDIQUE, RAO MUHAMMAD; UL HASSAN, MUHAMMAD JAWAD; RIZWAN, HAFIZ MUHAMMAD (Journal of the Hellenic Veterinary Medical Society, 2018)
Ticks and tick-borne infections pose major economic threats to the livestock industry throughout the world. The present study reports the point prevalence of ticks in the free range livestock population of the plain and hilly areas of Khyber Pakhtunkhwa (Mansehra, Haripur, Shangala, Kohistan), and Gilgit Baltistan (Diamer, Gilgit, Astor) along the Karakoram highway. Through convenient and snowball sampling techniques, a total of 813 animals, consisting of 232 sheep, 163 cattle, 365 goats and 53 buffaloes were screened for their tick burden. During the study, the two tick species identified were Hyalomma anatolicum and Rhipicephalus microplus. The overall prevalence of tick infestation among the screened livestock was 75.03%, with the highest distribution in sheep (81.47%) followed, in order, by cattle (77.91%), goats (72.05%) and buffalo (58.49%). The district-wise prevalence of ticks was the highest in Haripur (85.58), followed, in order, by Gilgit (83.10%), Mansehra (81.14%), Batagram (81.05%), Shangala (77.78%), Kohistan (75.38%), Diamer (72.28%) and Astor (32.22%). The prevalence of ticks was found to be higher (85.67%) in younger livestock than adults (66.44%), and in females (80.33%) than males (66.44%). The present study provides the first report of the tick distribution in higher altitudes of northern Pakistan and confirms the presence of Hyalomma and Rhipicephalus ticks in the plains, as well as the hilly geoclimates of Pakistan. Furthermore, the data on risk factors allows us to make recommendations to restructure the existing husbandry system of northern areas of Pakistan with the aim of reducing the tick burden on livestock.